Contrastive Research on Verbs of Visual Perception in Serbian and Slovenian - Takherboucht, Ana (Poznańskie Studia Slawistyczne, 2024)
The paper is a review that examines the semantic and syntactic analysis of verbs of visual perception in standard Serbian and standard Slovenian presented by Željko Marković in the monograph entitled Verbs of Visual Perception in Serbian and Slovenian: A Contrastive Semantic-Syntactic Analysis. The monograph was published in 2023 by the Faculty of Philosophy, University of Novi Sad, Serbia. The study investigates the semantic and syntactic properties of verbs of visual perception in Serbian and Slovenian from the perspective of contrastive linguistics. The author introduces the situation analysis of the perception act, which determines the properties relevant to the semantic description of this lexical semantic field of the verbs, and also investigates their predicate-argument structure.